Tectonics of the New Siberian Islands archipelago: Structural styles and low-temperature thermochronology. (November 2018) - Prokopiev, Andrei V.; Ershova, Victoria B.; Anfinson, Owen; Stockli, Daniel; Powell, Jeremy; Khudoley, Andrei K.; Vasiliev, Dmitry A.; Sobolev, Nikolay N.; Petrov, Eugeny O.
Abstract: Tectonic evolution of the New Siberian Islands (NSI) has been revealed based on detailed structural investigations and a (U-Th)/He low-temperature thermochronologic study of detrital zircons (ZHe) and apatite (AHe). Our study supports models claiming a non–Siberian affinity of the NSI and furthermore suggests that the study area formed a part of the Arctic-Alaska-Chukotka microcontinent. Seven stages of deformation have been revealed. The earliest stage (Stage 1) involved contractional deformation with transport directions towards the W-to WSW and occurred during the Late Cambrian across the De Long Islands. The next episode of deformation (Stage 2) has been revealed based on the low-temperature thermochronology (ca. 378–414 Ma, ZHe) and structural data. A pre-Frasnian angular unconformity formed as a result of Stage 2 deformation on Kotel'nyi Island, which involved contractional deformation with S-to SW transport directions (modern coordinates) in the mid-Paleozoic. In the latest Early Cretaceous–Late Cretaceous, three deformation stages were initiated by collision between the western part of the Arctic-Alaska-Chukotka microcontinent and Siberia, forming the South Anyui suture zone and overlapping orogenic belt. Stage 3 was characterized by the formation of major NW-trending folds, thrusts, and both transfer dextral and sinistral strike-slip faults with a reverse component. During Stage 4, the Arctic Alaska-Chukotka microcontinent moved westward. On Bolshoy Lyakhovsky Island, sinistral strike-slip faults were formed, whilst E-W compression took place across the Anjou islands. In Stage 5, the Arctic Alaska-Chukotka microcontinent shifted southward, forming a series of N-S-trending dextral strike-slip faults. The ZHe and AHe ages (ca. 93–125 Ma) suggest that these deformation events were associated with significant uplift in the western part of the NSI (Kotel'nyi and Bel'kovsky islands), whilst the eastern part (De Long Islands) was marginally affected by these events without significant uplift. The Cenozoic extension event (Stage 6) corresponds to the opening of the Eurasian Basin. This stage is manifested by the cooling episode (ca. 53 Ma, Early Eocene, AHe) established in the eastern part of the NSI (Jeannette Island). The origins of the late Cenozoic contractional deformations described from the Cenozoic deposits of the Anjou Islands (Stage 7) are unclear, but were possibly caused by movements along the Eurasian and North-American lithospheric plates.